Research and Application on Communication Resource Management System in Nuclear Power Plants - Kai Ji (Dianxin kexue)
In order to unify communication resources management of nuclear power plant，ensure the communication network work high reliably，reduce the maintenance cost and increase its work efficiency，the communication resource management system for nuclear power plants was designed and built. Through the management platform，communication system work efficiency was improved，strong support for higher authorities was provided to macro management communication resources，paperless work was achieved in communication field，all the communication resources such as communication wiring layout，voice equipments，power grid communication information were collected and managed automatically. As an outcome，an one-stop communication management system for users application，resources distribution，inquiry and answer，and automatic statistics was came to work.